A bioinspired three-dimensional graphene/chitosan hybrid scaffold for bone tissue engineering - Xue, Jingwen (2019)
An important aspect of bone tissue engineering (BTE) is bone regeneration, an interdisciplinary process involving the use of cells, biomaterials, and therapeutic agents. Biomaterials, being an essential part of this process, still face challenges in mimicking the three-dimensional (3D) architecture of natural bone and inducing the functions of cells and tissues during bone tissue formation. Electrical stimulation (ES), as one of the signals governing the functions of cells and tissues, has been proved to induce the bone formation of damaged tissues in vivo with outstanding efficiency. However, the research on its potential to improve the performance of bone regeneration with tissue-engineered materials in vitro has been challenging due to the lack of conductive 3D scaffolds. It has been found that graphene with great conductivity could be hybridized to conductive 3D scaffolds composited with biocompatible chitosan (CHI). Thus, it could be hypothesized that assembling graphene and CHI into a 3D construct mimicking the environment of bone tissues and the conductive property for the functioning of ES could generate a novel conductive hybrid scaffold for bone tissue applications.